Dampak Price Discount, Hedonic Shopping Motivation, dan Shopping Lifestyle terhadap Impulse Buying pada Konsumen TikTok Shop (Studi Kasus pada Mahasiswa Manajemen S1 Kampus STIE KBP Padang) - Mandasari, Alna; Sophian, Sophan (Lembaga Yasin AlSys, 2025)
The high frequency of impulse buying on the TikTok Shop platform, particularly among students, has not been accompanied by a comprehensive understanding of its driving factors. This study aims to analyze the impact of price discount, hedonic shopping motivation, and shopping lifestyle on impulse buying among TikTok Shop consumers, focusing on S1 Management students at STIE KBP Padang. A quantitative approach with a causal associative design was applied. A sample of 92 respondents was selected from a population of 1,095 students using purposive sampling, with the sample size determined using the Slovin formula at a 10% margin of error. Data were collected through a closed-ended questionnaire that was tested for validity and reliability, then analyzed using SPSS version 21 with multiple linear regression analysis and hypothesis testing (t-test). The results of the study indicate that price discount has a positive and significant effect on impulse buying, showing that price reductions encourage spontaneous purchasing decisions. Hedonic shopping motivation also significantly influences impulse buying, indicating that the pleasure derived from shopping is a key driver. Additionally, shopping lifestyle significantly affects impulse buying, implying that students' shopping habits and lifestyle influence their tendency to make unplanned purchases. This research provides practical implications for e-commerce businesses, particularly TikTok Shop, in designing promotional strategies and shopping experiences that align with the characteristics of young consumers to effectively boost impulse buying.